Pelatihan dan Pendampingan Pembuatan Prototipe E-Modul Interaktif Melalui Book Creator bagi Guru SD di Lembaga Pendidikan Maarif NU Kota Surabaya - Ghufron, Syamsul; Nafiah, Nafiah; Kasiyun, Suharmono; Rulyansah, Afib; Susanto, Rudi Umar (Universitas Islam Nahdlatul Ulama Jepara, 2023)
In general, elementary schools in the Maarif NU Educational Institution in Surabaya City do not have IT-based learning laboratories so that learning is always carried out in class. In addition, learning is still dominant using conventional media, namely blackboards and books, rarely using computer media. This happens because of the lack of teachers who understand the creation and use of computer-based learning media. Therefore, in an effort to utilize technology in learning, it is necessary to hold training on making e-modules with Book Creator. The methods for implementing this activity are as follows: field observations, analyze partner needs and offer solutions, make system designs, create materials related to interactive and interesting e-modules through book creators, carry out training and assistance in accordance with the title of community service, and conduct evaluation and reflection activities. This service activity was considered very successful. This success can be seen from the analysis of partner needs and the results of the t-test which show a significant value of the participants' competence before and after participating in the training. Thus, it can be concluded that this training and mentoring activity succeeded in increasing the digital literacy skills of the training participants.